2016
DOI: 10.1007/s00401-016-1639-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous low-grade neuroepithelial tumor of the young (PLNTY): an epileptogenic neoplasm with oligodendroglioma-like components, aberrant CD34 expression, and genetic alterations involving the MAP kinase pathway

Abstract: Epileptogenic tumors affecting children and young adults are a morphologically diverse collection of neuroepithelial neoplasms that, as a group, exhibit varying levels of glial and/or neuronal differentiation. Recent advances in molecular profiling technology, including comprehensive DNA sequencing and methylation analysis, have enabled the application of more precise and biologically relevant classification schemes to these tumors. In this report, we describe a morphologically and molecularly distinct epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
255
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(264 citation statements)
references
References 47 publications
5
255
1
3
Order By: Relevance
“…As previously noted (24,45), some features of MVNT align more with a malformation of cortical development or dysplasia than a neoplasm, supported by evidence in this current study. This includes (i) the lack of any growth on serial MRI or reported regrowth, even following incomplete resection, (ii) no overt increase in cellularity or conspicuous mitotic activity, (iii) lack of expansive or infiltrative growth patterns with nodules 'sitting' in an undisturbed laminar cortex, (iv) comparable localizations in deep cortex/subcortical region in reported cases, (v) retained expression of immature, developmentally regulated proteins as SOX2, TBR1, OTX1, KCC1 and GFAPo, (vi) absence of any of the known genetic abnormalities of LEATs following NGS, including BRAF V600E, MYB and FGFR1 mutations (15,25,42,44,47,50) and (vii) NGS in the present study showing recurring synonymous SNPs in SMO and DEPDC5 in common with cortical dysplasia (FCD IIB) and NPRL3 SNPs noted frequently in MNVT and FCD but not other glioneuronal tumors. Copy number variations in SMO a receptor in the Shh pathway have been recently shown in hypothalamic hamartoma associated with gelastic seizures (22) and DEPDC5 and NPRL3 mutations reported in FCDII (5,56).…”
Section: Neoplasia or Malformationmentioning
confidence: 99%
“…As previously noted (24,45), some features of MVNT align more with a malformation of cortical development or dysplasia than a neoplasm, supported by evidence in this current study. This includes (i) the lack of any growth on serial MRI or reported regrowth, even following incomplete resection, (ii) no overt increase in cellularity or conspicuous mitotic activity, (iii) lack of expansive or infiltrative growth patterns with nodules 'sitting' in an undisturbed laminar cortex, (iv) comparable localizations in deep cortex/subcortical region in reported cases, (v) retained expression of immature, developmentally regulated proteins as SOX2, TBR1, OTX1, KCC1 and GFAPo, (vi) absence of any of the known genetic abnormalities of LEATs following NGS, including BRAF V600E, MYB and FGFR1 mutations (15,25,42,44,47,50) and (vii) NGS in the present study showing recurring synonymous SNPs in SMO and DEPDC5 in common with cortical dysplasia (FCD IIB) and NPRL3 SNPs noted frequently in MNVT and FCD but not other glioneuronal tumors. Copy number variations in SMO a receptor in the Shh pathway have been recently shown in hypothalamic hamartoma associated with gelastic seizures (22) and DEPDC5 and NPRL3 mutations reported in FCDII (5,56).…”
Section: Neoplasia or Malformationmentioning
confidence: 99%
“…Methylation profiles were compared to a reference cohort of 2150 cases from 77 tumor entities previously profiled and analyzed at German Cancer Research Center using a random forest algorithm and customized bioinformatics packages. In addition, the array data was used to calculate a low-resolution copy number profile (CNP) as previously described by others [7,8] and us [9,10]. Analysis was performed on specimens at the time of initial diagnosis.…”
Section: Genome-wide Methylation Profilingmentioning
confidence: 99%
“…Since then multiple other activating alterations of RAS/MAPK pathway have been described in pediatric LGG, and it has been suggested that LGGs of childhood are a single pathway disease (Fig. ) …”
Section: Epidemiologymentioning
confidence: 99%
“…2). [17][18][19][20][21] Interestingly, PA is the most frequent type of LGG in children and has a very good prognosis. 26 Indeed, the molecular classification of gliomas in adults has been rapidly replacing the traditional morphological-based schemes currently in place.…”
Section: Epidemiologymentioning
confidence: 99%